The Inhibitory Effect of Leaves and Stems of Nerium oleander Alcoholic and Aqueous Extracts on Some Fungi In Vitro - AL-RazaqJameel, Fadwa Abdul (The Iraqi Journal of Veterinary Medicine, 2011)
The objective of the current study was to evaluate the effect of alcoholic and aqueous extract for leaves and stems of Nerium oleander on Trichophyton mentogrophytes and Cryptococcus neoformens in vitro. The effect of alcoholic extract for Nerium oleander leaves and stems on the tested fungi was showed inhibitory effect specialy on Trichophyton mentogrophytes compared with aqueous extract of leaves and stems of plant which showed less or no inhibition against the tested fungiA high inhibition rate of alcoholic extract of leaves and stems of plant aginst Trichophyton mentogrophytes were 83.3% and 67% respectively in concentration 20mg/ml. But the inhibition rate of aqueous extract of leaves and stems of plant on the same fungus were 30% and 0%respectively, in concentration 20mg/ml. The other aspect of the current study for the effect of alcoholic and aqueous extracts leaves and stems against Cryptococcus neoformens was done by measuring the diameter of inhibition zone of alcoholic extract of leaves and stems of the plant were 30mm and 22mm respectively in aconcentralion 200mg/ml where no inhibition zone for the aqueous extracts of leaves and stems of the plant against Cryptococcus neoformens. The conclusion of this study revealed that the Nerium oleander plant ( Toxic plant ) can be used as antifungal particulary the alcoholic extract of leaves and stems agairst Trichophyton mentogrophytes and Cryptococcus neoformens.